POTENTIAL OF TOURISM OBJECTS ON THE ECONOMY OF THE COMMUNITY OF LENJU VILLAGE, NORTH SOJOL DISTRICT, DONGGALA DISTRICT - Darise, Ramlah Ilham; Resky, Moh. (Universitas Muhammadiyah Luwuk Banggai, 2023)
Objective Study This is , for know is Potency Object Tour Sand White To Economy Community in the Village Lenju And For recognize constraint What just what you get For develop the potential that exists in Pasir White as well as How the solution.Based on results study with study qualitative.Researcher do interview to related sources _ with object tour Sand White And obtain that Sand White own potentials naturally possible _ developed For increase Income Native to the Village Lenju And influential to economy public around with opportunity business as well as opportunity work.Keywords: Potential Object TourÂ And Growth Economy Society.